PENGARUH KUALITAS PELAYANAN, LOKASI DAN PROMOSI TERHADAP KEPUTUSAN PEMBELIAN AISYAH BROWNIES BATAM - Rizaldo, Nofan; Winda Evyanto (SCIENTIA JOURNAL, 2022)
Batam is one of the leading industrial cities in Indonesia and also one of the main entrances for the entry of foreign and domestic tourists. Batam is the main gateway to the inflow of foreign tourists in Kepulauan Riau. With a good quality of service then a strategic location and also attractive promotions carried out so that potential consumers know the existence of the products offered, this will be the beginning for consumers to make a purchase decision. This study aims to find out whether there is a partial or simultaneous influence between the quality of service, location and promotion on purchasing decisions at Aisyah Brownies Batam. The population in this study was 516 consumers of Aisyah Brownies Batam. The number of samples used was 225 people. Data collection techniques using questionnaires. The research method used is the quantitative method. The data is processed using the SPSS version 26 program. The results showed a significant influence of service quality on purchasing decisions with t test 2,247 > t table 1,651, a significant impact of location was found on purchasing decisions with t test 3,965 > t table 1,651, and also promotions had a significant impact on purchasing decisions with t value 2,376 > t table 1,651. This research also proves that simultaneously the quality of service, location and promotion affects the purchasing decision at Aisyah Brownies Batam with the result of a calculated f value of 24.901 > f table 2.645